Sustaining Biodiversity and Ecological Roles in a Heritage Landscape: The Role of Coffee Agroforestry in Kluncing, Indonesia - Kurnianto, Agung Sih; Dewi, Nilasari; Sulistyowati, Hari; Siddiq, Arif Mohammad; Ratnasari, Tri; Khowatini, Husnul; Yulianto, Roni; Firdaus, Anggun Sausan (HAYATI Journal of Biosciences, 2025)
This study investigates the role of coffee agroforestry in sustaining biodiversity and ecosystem functions in Kluncing, Ijen, Indonesia. By quantifying bird, butterfly, and coffee insect diversity using the Shannon-Wiener index, it evaluates ecological dynamics and their implications for sustainable land management. Bird communities demonstrated the highest diversity (2.911), indicating ecosystem stability, while butterflies (2.481) and coffee insects (1.841) exhibited lower diversity, reflecting habitat and resource limitations. Trophic network modeling using NetworkX identified keystone species like Collocalia linchi (21.9% relative abundance) among birds and the Formicidae family (29.8% relative abundance) among coffee insects, emphasizing their critical roles in ecosystem balance. Canonical Correspondence Analysis (CCA) highlighted the influence of environmental factors on species distribution. Species such as Ariadne ariadne and Delias belisama were sensitive to humidity and temperature, while Collocalia linchi favored areas with higher light intensity. The findings underscore the importance of tailored management practices to address species-specific responses to microclimatic variations. Sustainable agroforestry management is vital for preserving biodiversity, maintaining ecosystem stability, and ensuring agricultural productivity. This study also highlights challenges posed by habitat degradation and climate change, emphasizing the need for adaptive strategies to safeguard this unique agroforestry landscape.